PREDIKSI KETERSEDIAAN BERAS DI MASYARAKAT DENGAN MENGGUNAKAN LOGIKA FUZZY DAN JARINGAN SYARAF TIRUAN DALAM UPAYA MENINGKATKAN KETAHANAN PANGAN - M FM Fuad (AGROINTEK, 2011)
Development to predicted Handling availability of food stocks need to be done, one by combining model predictions using fuzzy logic and artificial neural network or more in the know with ANFIS (Adaptive Neuro Fuzzy Inference System). Predicted availability of the study aimed to obtain the status of availability of rice in the community by using fuzzy logic and artificial neural network, which later can provide food security in the region. Artificial neural network and fuzzy logic can be used in building an intelligence system to predict the value of the availability of rice in the community. This can be seen from the results of research in which the system was developed using the artificial neural network, and fuzzy logic in general can be said is able to predict the value of the availability of rice in the community with the prediction error is 0.3873 where input from the system we provide is almost exact, with the level of error is relatively small.